St. Clements House at 61 West Brookline Street across from Blackstone Square, ca. 1958 - Unknown (Tufts Archival Research Center, 2005)
Detail of the upper levels, roof, and cupola or lantern of 61 West Brookline Street, between Shamut Avenue to the west and Washington Street to the east. The facade of the home faces southwest across West Brookline Street towards Blackstone Square. Photograph used to illustrate an article by Lawrence for the Boston Globe; former home of Nathaniel and Justin Winsor; designed by Gridley J. F. Bryant 6 15/16 x 4 5/8 Photographs